Kesetiaan Allah Sebagai Model Kesetiaan Orang Beriman Kristiani Menurut Teks Roma 11:25-32 - Kore, Yolenti Tay; Olla, Yasinta; Katoda, Anjelina; Dopong, Florentina; Mari, Angelina Marici Kewa; Abuk, Fransiska Uny; Senda, Siprianus S.; Taninas, Gaudensius (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Loyalty is an important element in the life of Christian faith. Christian faith requires loyalty in order to persist in a faith that is always full of challenges. Believers are often unfaithful when facing certain challenges. Therefore, a model of loyalty to the truth is needed. Paul in his letter to the church in Romans 11:25-32 describes God's faithfulness as a model of true faithfulness. This research aims to examine Paul's ideas and find a comprehensive picture of God's faithfulness. The research method used is library research with a descriptive analysis approach. From various references, both the Holy Bible and books and scientific articles related to this theme. God's faithfulness throughout Scripture shines through in the fullness of His promises. According to Paul, God's righteousness lies in His faithfulness to His promise of salvation. Humans respond to God's faithfulness by holding fast to the promised promises of faith. Abraham's faith is a concrete example of human experience in responding to God's faithfulness. He never rejects people who are faithful to His covenant.